2019
DOI: 10.1177/0021909619865582
|View full text |Cite
|
Sign up to set email alerts
|

“We Sleep with One Eye Open”: Exploring the Experiences of Churches in Rivers State, Nigeria

Abstract: In instances of insecurity in many societies, churches “also” suffer. Yet there is a dearth of literature exploring the experiences of churches in connection with situations of insecurity. This study, therefore, explored the experiences of churches in the face of the high rate of insecurity in Rivers State, Nigeria. Information was elicited from 16 church leaders of different denominations in different communities in Rivers State. Using a descriptive narrative approach, the study found that churches’ experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The more fundamental factor as identified by participants was youth unwillingness to work. In fact, with the revealing of this factor such as youth unwillingness to work, the present study particularly challenges what seems to be the dominant view in the body of literature, that of deprivation/marginalization and youth unemployment being the major reasons or factors responsible for crime and youth restiveness in the Niger Delta, especially in Rivers State (see Ejibunu, 2007;Nche et al, 2019;Nwogwugwu et al, 2003;Uyang et al, 2016). According to participants, most youths in Rivers State consumed with the get-rich-quick syndrome mentality desire to get rich without showing corresponding desire to work.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The more fundamental factor as identified by participants was youth unwillingness to work. In fact, with the revealing of this factor such as youth unwillingness to work, the present study particularly challenges what seems to be the dominant view in the body of literature, that of deprivation/marginalization and youth unemployment being the major reasons or factors responsible for crime and youth restiveness in the Niger Delta, especially in Rivers State (see Ejibunu, 2007;Nche et al, 2019;Nwogwugwu et al, 2003;Uyang et al, 2016). According to participants, most youths in Rivers State consumed with the get-rich-quick syndrome mentality desire to get rich without showing corresponding desire to work.…”
Section: Discussionmentioning
confidence: 56%
“…This, according to the authors, was because of the disappointment they received from political elites to whom they served as thugs during electioneering periods. This highlights the complexity of the security situation in the region, especially Rivers State (Nche et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study employed a deductive approach in the analysis of the interview data. In applying this approach, the researchers, in line with the Colaizi's guide (as cited in Nche, 2021;2020a, 2020b, 2020cNche et al, 2019)…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the Muslim and Christian communities and places of worship constitute the sectors that are mostly affected by the attacks carried out by Boko Haram across Lake Chad with over 2134 fatalities recorded across both communities in 2018 (see Nigeria Watch 2019). These attacks further affected the already deplorable and tense Christian-Muslim relations that have characterized most of the conflicts and tensions between these two religions in recent years (Michael Kpughe 2017; Faseke 2019; Nche et al 2019).…”
Section: Response From Faith-based Organizations and Civil Society Ormentioning
confidence: 99%